Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure, let's go through the steps to solve the equation [tex]\(3x^2 + 3y^2 = 0\)[/tex]:
1. Divide the Equation by 3:
[tex]\[ 3x^2 + 3y^2 = 0 \][/tex]
Dividing both sides of the equation by 3 simplifies the equation:
[tex]\[ x^2 + y^2 = 0 \][/tex]
2. Analyze the Equation [tex]\(x^2 + y^2 = 0\)[/tex]:
Notice that [tex]\(x^2\)[/tex] and [tex]\(y^2\)[/tex] are both squared terms, which means they are both non-negative (i.e., [tex]\(x^2 \geq 0\)[/tex] and [tex]\(y^2 \geq 0\)[/tex]). The sum of two non-negative terms equals zero only if both terms are zero.
3. Set Each Term to Zero:
Therefore, for the equation [tex]\(x^2 + y^2 = 0\)[/tex] to hold true, both:
[tex]\[ x^2 = 0 \][/tex]
and
[tex]\[ y^2 = 0 \][/tex]
4. Solve for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
If [tex]\(x^2 = 0\)[/tex], then the only solution is:
[tex]\[ x = 0 \][/tex]
Similarly, if [tex]\(y^2 = 0\)[/tex], then the only solution is:
[tex]\[ y = 0 \][/tex]
Therefore, the solution to the equation [tex]\(3x^2 + 3y^2 = 0\)[/tex] is:
[tex]\[ (x, y) = (0, 0) \][/tex]
This means both [tex]\(x\)[/tex] and [tex]\(y\)[/tex] must be zero to satisfy the original equation.
1. Divide the Equation by 3:
[tex]\[ 3x^2 + 3y^2 = 0 \][/tex]
Dividing both sides of the equation by 3 simplifies the equation:
[tex]\[ x^2 + y^2 = 0 \][/tex]
2. Analyze the Equation [tex]\(x^2 + y^2 = 0\)[/tex]:
Notice that [tex]\(x^2\)[/tex] and [tex]\(y^2\)[/tex] are both squared terms, which means they are both non-negative (i.e., [tex]\(x^2 \geq 0\)[/tex] and [tex]\(y^2 \geq 0\)[/tex]). The sum of two non-negative terms equals zero only if both terms are zero.
3. Set Each Term to Zero:
Therefore, for the equation [tex]\(x^2 + y^2 = 0\)[/tex] to hold true, both:
[tex]\[ x^2 = 0 \][/tex]
and
[tex]\[ y^2 = 0 \][/tex]
4. Solve for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
If [tex]\(x^2 = 0\)[/tex], then the only solution is:
[tex]\[ x = 0 \][/tex]
Similarly, if [tex]\(y^2 = 0\)[/tex], then the only solution is:
[tex]\[ y = 0 \][/tex]
Therefore, the solution to the equation [tex]\(3x^2 + 3y^2 = 0\)[/tex] is:
[tex]\[ (x, y) = (0, 0) \][/tex]
This means both [tex]\(x\)[/tex] and [tex]\(y\)[/tex] must be zero to satisfy the original equation.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.